Corps vivante - Delporte, Julie (Éditions Pow Pow, 2022)
"En 1990, Julie Delporte n'a encore jamais vu de butch, mais sa tante préférée chasse et fume le cigare. Presque vingt ans plus tard, elle publie un livre sur Tove Jansson dans lequel elle raconte avec joie que cette artiste finlandaise est la première femme à qui elle s'identifie, seulement elle était lesbienne et pas Julie. À 35 ans, après avoir surligné de toutes les couleurs son exemplaire de La pensée straight de Monique Wittig, Julie Delporte arrête de porter des robes et prend son avenir en main. Dans ce roman graphique qui fait suite à Moi aussi je voulais l'emporter, l'autrice retrace l'histoire de sa sexualité. Une histoire marquée par la violence malheureusement trop banale des agressions, comme par celle des clichés et des injonctions liés à une culture de la performance et de l'hétéronormativité."--
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; autofiction; bande-dessinée; canada; corps; cours; discipline; europe; france; har4600; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; queer; québec; roman graphique; régions géographiques; sexualité; thématiques; violences; études littéraires

Gender (in)securities: Surveillance and transgender bodies in post 9/11 era of neoliberalism - Quinan, Christine (Security/mobility: politics of movement, 2017)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; citoyenneté; corps; genre; hétérosexisme; identités; législation; personnes trans*; périodes historiques; queer; racisme; ressource en ligne; solidarité; systèmes d'oppressions; thématiques; violences

Le bouclier thérapeutique: discours et limites d’un appareil de légitimation - Espineira, Karine (Le sujet dans la cité, 2011)
En 1982, le professeur René Küss plaide à la télévision pour un protocole appelant à distinguer entre « vrais » et « faux » trans’ : de « vrais trans’ » ne causent aucun trouble dans le genre : on leur accorde une aide exceptionnelle (l’opération) par laquelle - hommes devenus femmes ou femmes devenues hommes - ils rentrent dans l’ordre du genre et de l’identité. Telle est l’une des premières expressions de ce que nous proposons d’appeler le « bouclier thérapeutique ». Les trois décennies qui suivent voient s’affronter les affirmations transidentaires et l’idéologie dominante des « traitants ». Appareil de légitimation d’un ordre ancien, le « bouclier thérapeutique » ne serait-il plus aujourd’hui pour ses partisans que le dernier vestige d’une ère marquée par l’effritement d’un deuxième bouclier, juridique celui-ci, garantissant que la libre disposition de l’état civil reste une exception ? Sur ces questions qui interrogent profondément les représentations que nos sociétés se font d’elles-mêmes, peut-être le temps est-il venu d’ouvrir la route tracée par la recherche en sciences sociales et humaines aux nouveaux paradigmes amorcés par les Études de Genre.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; care; cours; discipline; discours; europe; france; inégalités; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; transféminisme; violences; violences institutionnelles; violences médicales

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis